Pastoral Theological Reflections on Deification from a Lutheran Perspective - Jonathan Linman (Religions, 2025)
In this article, I explore deification in light of the practice of pastoral ministry in Lutheran settings, engaging the biblical witness and key features of the Lutheran theological tradition as sources for understanding deification from a Lutheran perspective. Through this study, I have come to view deification from a Lutheran perspective as our union with Christ in faith, individually and communally embodied, that is generated by the energies of the Holy Spirit working through the means of grace in the church for the sake of advancing God’s mission in the world.